Tightly-Packed Repetitive Schedules: A Tetris Challenge. Issue 1 (January 2022) - Hegazy, T; Mostafa, K
Abstract: A large portion of new and rehabilitation projects for the civil infrastructure involves repetitive tasks that mandate high degree of synchronization among the resources to meet project constraints. Despite their large need for support, few tools exist commercially. This is due, in part, to the computational and visualization challenges of existing repetitive scheduling techniques, which complicate the process and make it less understood, particularly when the repetitive units are not identical and when resources are limited. This presentation introduces enhancements by dealing with repetitive scheduling as a game of Tetris, where tasks can change geometry to fit tightly together to save project duration. This is demonstrated through novel mathematical formulations, as well as a new heuristic scheduling algorithm (First-Come-First-Serve). It will be shown that the proposed geometrical adjustments are more advantageous in improving repetitive schedules than using expensive accelerations, and the new visuals make the schedule more legible. This research is a step towards making repetitive scheduling a mainstream tool, to benefit the construction industry.